Strategic use of observer-perspective questions in couples therapy - Muntigl, Peter; Horvath, Adam O. (Frontiers in Psychology, 2023)
Questions are one of the most frequently used strategies in therapy. There is a body of theoretical work on the kinds of questions that are preferred in specific treatment approaches. But research on the use of questions in general, how they are formed, what specific therapeutic work they do is relatively scarce in the literature. In this paper we use the conceptual framework and methods of Conversation Analysis (CA) to examine how systemic questions soliciting clients’ perspective on the partners’ thoughts and intents (Observer-Perspective Questions; OPQs) are realized interactively in actual clinical practice and the range of therapeutic work they perform in couples therapy. We identified 78 OPQs from archival data of videotaped time-limited couples therapies, a clinical population working with a professional therapist. From this set of 78 OPQs five excerpts representing diverse use of OPQs were selected. These excerpts were transcribed in detail capturing not only the textual content but also the prosodic, gestural, and non-verbal aspects of these episodes. Using CA methodology, we identified four specific kinds of changes these questions can promote: progress toward relational optimism, support of positive aspects of the couple’s relationship, promoting the concept that the couples’ experiences and emotions are interlinked, and introducing new creative relational options. Detailed CA analyses of these clinical excerpts allowed us to identify how the OPQ sequences were built to realize these therapeutically useful moves using various conversational resources progressively and interactively. The conversational analysis of these sequences facilitated the exploration of relationships between the ways the questions are formed, timed, and delivered and the specific functions they perform to move the therapy forward. In conclusion we make the general argument that examining important therapy events through a CA perspective provides a significant complimentary vector to quantitative research on therapy process.